2019
DOI: 10.1111/tpj.14293
|View full text |Cite
|
Sign up to set email alerts
|

The macrocyclizing protease butelase 1 remains autocatalytic and reveals the structural basis for ligase activity

Abstract: Plant asparaginyl endopeptidases (AEPs) are expressed as inactive zymogens that perform maturation of seed storage protein upon cleavage-dependent autoactivation in the low-pH environment of storage vacuoles. The AEPs have attracted attention for their macrocyclization reactions, and have been classified as cleavage or ligation specialists. However, we have recently shown that the ability of AEPs to produce either cyclic or acyclic products can be altered by mutations to the active site region, and that severa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 47 publications
9
76
0
Order By: Relevance
“…We modelled a succinimide intermediate (SNN) at Asp157 to obtain a better fit with the electron density at this position (Supplemental Figure 9A). The presence of SNN is consistent with all other plant structures except OaAEP1 (Yang et al, 2017;Haywood et al, 2018;Zauner et al, 2018b;Hemu et al, 2019;James et al, 2019), although OaAEP1 does have electron density suggesting that succinimide may in fact be present (James et al, 2019). Gln335, which is part of the cap domain, occupies the S1 pocket of the active site in the zymogen (according to nomenclature by Schechter and Berger where P1, P2 and so on refer to residues N-terminal to the cleavage site, whereas P1′, P2′ and so on are C-terminal to it, and where the corresponding binding sites on the protease are termed S2, S1, S1′, S2′, etc.)…”
Section: Ceaep1 Active Site Residues Are Strictly Conservedsupporting
confidence: 85%
See 2 more Smart Citations
“…We modelled a succinimide intermediate (SNN) at Asp157 to obtain a better fit with the electron density at this position (Supplemental Figure 9A). The presence of SNN is consistent with all other plant structures except OaAEP1 (Yang et al, 2017;Haywood et al, 2018;Zauner et al, 2018b;Hemu et al, 2019;James et al, 2019), although OaAEP1 does have electron density suggesting that succinimide may in fact be present (James et al, 2019). Gln335, which is part of the cap domain, occupies the S1 pocket of the active site in the zymogen (according to nomenclature by Schechter and Berger where P1, P2 and so on refer to residues N-terminal to the cleavage site, whereas P1′, P2′ and so on are C-terminal to it, and where the corresponding binding sites on the protease are termed S2, S1, S1′, S2′, etc.)…”
Section: Ceaep1 Active Site Residues Are Strictly Conservedsupporting
confidence: 85%
“…CeAEP1 is structurally similar to previously solved plant AEP structures: Helianthus annuus AEP1 or HaAEP1 6AZT (Haywood et al, 2018), AtLegγ 5NIJ (Zauner et al, 2018b), Oldenlandia affinis AEP1 or OaAEP1 5H0I (Yang et al, 2017), Viola yedoensis peptide asparaginyl ligase 2 or VyPAL2 6IDV (Hemu et al, 2019), and butelase1 6DHI (James et al, 2019) with an r. m. s. d. of 1.0-1.1 Å over 400-430 Cαatoms between CeAEP1 and the other published structures (Supplemental Table 2). The zymogen is made up of a 'core' domain (Glu38-Asp313) linked to a C-terminal 'cap' domain (Arg336-Ala474) via the flexible linker, which has weak electron density (Figure 6A).…”
Section: Jack Bean Aep Structuresupporting
confidence: 73%
See 1 more Smart Citation
“…Previous studies showed that the AEP domain in prolegumain is present already in an active conformation ( 21 , 34 ). Zymogenicity resulted solely from the steric blockage of the active site by the AP and LSAM domain.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple reaction monitoring (MRM) was carried out exactly as described previously (94), except trypsin was added to the protein samples in a mass ratio of 1:20. Peptide abundances from each sample were normalised against VDAC in which its abundance was identical between mitochondria from Col-0, dic2-1 and dic2-1/gDIC2 based on western blotting.…”
Section: Methodsmentioning
confidence: 99%